Factors Influencing Baby Boomers And Gen X ‘s Intention To Use Cashless Payment in Batu Pahat, Johor - lew, mei shi; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2024)
Privacy concerns and technological risks amplify challenges in adopting cashless transactions. Growing distrust, fueled by worries about data security and identity theft, hinders consumer willingness to embrace digital payments. This is particularly evident among the elderly, like baby boomers and Gen X, who face usability issues and prefer traditional payment methods due to limited digital currency knowledge and discomfort with technology. Overcoming these barriers is crucial for widespread cashless payment adoption. This study is aimed to identify the intention level of baby boomers and Gen X to use cashless payment in Batu Pahat. Besides, to identify the dominant factors influencing baby boomers and Gen X’s intention to use cashless payment in Batu Pahat. This study also todetermine the relationship between the factors and baby boomers and Gen X’s intention to use cashless payment in Batu Pahat. The study utilizes the Technology Acceptance Model (TAM) framework, which considers perceived usefulness, perceived ease of use, perceived risk, and trust as the key variables. Data collection for this study was conducted through an online questionnaire administered to respondents. A total of 384 questionnaires were distributed to participants, and 230 complete and valid sets of responses were received. The findings indicate a positive correlation between all variables and the intention to use cashless payment. This research is crucial for understanding and promoting cashless payments in Malaysia, especially among the elderly. It offers valuable insights for companies, particularly payment providers, to tailor services, increase awareness, and gain a competitive edge in the industry.